Improving quality and consumer acceptance of rabbit meat: prospects and challenges - Kumar, Pavan; Sharma, Neelesh; Narnoliya, Lokesh Kumar; Verma, Akhilesh Kumar; Umaraw, Pramila; Mehta, Nitin; Ismail-Fitry, Mohammad Rashedi; Kaka, Ubedullah; Goh, Yong-Meng; Lee, Sun-Jin; Sazili, Awis Qurni (Elsevier, 2025)
Rabbit meat is an excellent source of high-quality proteins, essential fatty acids, vitamins, and minerals, which can be further improved through various management, preslaughter, and post-slaughter interventions. Rabbit meat consumption is popular in certain regions of the world. The multidimensional role of rabbits as pet, pest, and laboratory animals, lack of proper knowledge among consumers towards the nutritive value of rabbit meat, animal welfare, and ethical issues, sustainable potential, undeveloped marketing, and processing chain, and price parity with available cheap meat and non-meat alternatives, are some constraints in the rabbit meat production. Increasing awareness of the nutritive value, positive health effects of rabbit meat consumption and production chain, development of processed meat products, and proper animal welfare compliance in rabbit production could improve consumer acceptance. The present manuscript reviewed various factors that affect the meat quality and consumer acceptance of rabbit meat for a more sustainable and viable source for global meat supply.